Contrasting reproductive and ecological traits affect the genetic diversity and fine-scale genetic structure of two sympatric and epiphytic tropical bromeliads - Huerta-Fahara, Sofía; Cristóbal-Pérez, E Jacob; Cascante-Marín, Alfredo; Madrigal-Brenes, Ruth; Fuchs, Eric J; Quesada, Mauricio (Botanical journal of the Linnean Society, 2025)
Tropical montane forests are highly diverse ecosystems with high levels of endemism. Within these habitats, epiphytic plants are among the most diverse and understudied species groups. Despite their diverse reproductive and ecological traits, their influence on genetic diversity and fine-scale genetic structure (FSGS) has rarely been studied. We assessed how reproductive and ecological traits affect genetic diversity and FSGS within and among phoropytes in two epiphytic bromeliads: Aechmea mariae-reginae, a dioecious, hummingbird-pollinated, and bird-dispersed species, and Werauhia ampla, a hermaphroditic, self-compatible, bat-pollinated, and wind-dispersed species. We collected leaf tissue from 93 A. mariae-reginae and 94 W. ampla individuals. We used eight microsatellite loci to describe genetic diversity, structure, and FSGS in both species. Genetic diversity was higher in A. mariae-reginae than in W. ampla. Genetic diversity was not affected by multilocus identical genotypes. Both species showed low genetic structure among phorophytes. Significant FSGS was found in distance classes below 25 m in A. mariae-reginae, but no FSGS was found in W. ampla. The reproductive and breeding system of these species affects genetic diversity, with the dioecious and animal-pollinated species having higher diversity estimates. Limited seed dispersal by social birds in A. mariae-reginae results in significant FSGS within phorophytes. The absence of FSGS in W. ampla is due to extensive seed dispersal by wind.